The International Society for Krishna Consciousness: Religion and Politics in West Bengal - Salter, Brian (Journal for the academic study of religion, 2013)
The State of West Bengal in India is the home of a monotheistic, salvationist religion known as Vaishnavism. It has also been governed for 30 years by the democratically elected Communist Party of India-Marxist (CPI-M). Vaishnavism has expanded globally, largely via the International Society for Krishna Consciousness (ISKCON or the Hare Krishna movement). ISKCON has developed an intentional community in West Bengal as its world headquarters, and this community is becoming one of the state's major tourist attractions and income-earners. The research that follows in this article was conducted to assess tensions between the West Bengal government and ISKCON, particularly in relation to land acquisition and workers' rights policies. Perceptions of a contemporary alliance between ISKCON and a Hindu nationalist party, the Bharatiya Janata Party (BJP), which is a rival to the government and has historical ties to ISKCON, are found to be aggravating politics at the local level. The research highlights sensitivities at the intersection of religion, politics and culture, and the complexities of state-religion relationships in West Bengal.